Analysis of Foundation Testing Methods on The Aria Apartemen Batam Construction Project - Rizqi Azmi Arif; Pamadi, Mulia (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2024)
The Aria Apartment project is the construction of a modern apartment complex that requires a strong and safe pile foundation. To ensure the quality and strength of the piles, a PDA Test (Pile Driving Analyzer Test) is carried out. PDA Test is a non-destructive method used to measure the performance and integrity of piles by utilizing vibration waves produced during driving. In this project, the PDA Test was carried out to test the pile bearing capacity against dynamic loads, check the structural integrity of the pile, and ensure that the pile installation complies with the design specifications. This test provides data regarding ultimate compressive strength, energy transfer efficiency, and the possibility of defects or damage to the pile.The PDA Test results show that the piles used in the